HUBUNGAN KETERAMPILAN MEMBACA CERPEN DENGAN KETERAMPILAN MENULIS PUISI SISWA KELAS X SMAN 1 KECAMATAN AKABILURU KABUPATEN LIMA PULUH KOTA - Hendrisman Hendrisman (Ensiklopedia of Journal, 2019)
This research results can be seen three things. First, the skills to read short stories of students in grade X SMA Negeri 1 Akabiluru sub district in general is 75 who are in the range of 66-75% with more than enough qualification. Second, the skill of writing poetry of class X students of SMA Negeri 1 Akabiluru Sub district generally is 87 which is in 86-95% range with excellent qualification. Third, hukbungan skills to read short stories with the skills of writing poetry class X students SMA Negeri 1 Akabiluru with r value of 0.498. After analyzed by the t-test formula, obtained value t_hitung> t_table is 3.622340> 1.697 with dk n-2 (32-2 = 30) and significant level of 0.05 or 95%. From the results of the correlation can be concluded that there is a significant relationship between the skills of reading short stories with skills to write poetry class X students SMA Negeri 1 Akabiluru District.